The Influence of Ability and Motivation on Employee Performance on Company Progress - Muhtadi, Muhammad Ammar (West Science Journal Economic and Entrepreneurship, 2023)
The research aims to know and analyze how ability and motivation affect the performance of employees in the moving company. When viewed from its background, namely essential, in an organization, the Human Resources (HR) factor has an important role compared to other factors. Humans have a necessary function in achieving performance, so HR requires expertise that is quite reliable. Employee performance is a very dominant factor in improving company performance. The method used in this research is a method literature review. Namely a literature search conducted through Science Direct and Google Scholar. In the early stages of searching for articles, 406 journal articles were obtained using the keyword “employee performance.” The results showed that workability and motivation significantly influence the company's progress, and every ability possessed by employees must always coexist with work motivation to perfect it as the key to the company's success.